Modulation of LPS-associated virulence activity for reduction of periodontal inflammatory burden - Dong, Anbo; Lehto, Markku; Putaala, Jukka; Paju, Susanna; Pussinen, Pirkko; Zaric, Svetislav (Frontiers in Microbiology, 2026)
BackgroundDysbiotic oral biofilms produce virulence factors, such as lipopolysaccharide (LPS), triggering and sustaining chronic inflammation in periodontal tissues. Modulation of the bioactivity of these products offers a potential novel, adjunctive approach beyond conventional periodontal therapy.MethodsPooled saliva and subgingival biofilm samples from 324 healthy, gingivitis, and periodontitis participants were assessed for endotoxin activity using the recombinant Factor C (rFC) assay. Functional immune-stimulation was evaluated in THP-1 and THP-1 Dual cell models through NF-κB and IRF pathways activation assessment and cytokine profiling. The modulatory effects of antimicrobial peptide LL-37 and the LPS-binding compound Polymyxin B on saliva and subgingival biofilm inflammatory potential were assessed in the same models.ResultsRecombinant Factor C assays demonstrated marked reductions in endotoxin activity of saliva and subgingival biofilms treated with LL-37 and Polymyxin B (>90% reduction). Both NF-κB and IRF signaling were broadly attenuated following modulation, with polymyxin B exerting greater suppression of NF-κB activity, while LL-37 showed stronger inhibition of IRF, particularly in salivary samples. Pro-inflammatory cytokines secretion by THP-1 cells (IL-1β, IL-6, IL-8, and TNF-α) challenged with bio-modulated samples decreased by 40–75% compared to untreated samples. Interestingly, anti-inflammatory cytokines such as TGF-β and IL-10 remained largely unchanged, suggesting selective suppression of the cytokine cascade.ConclusionModulating LPS-associated virulence activity substantially reduces the inflammatory potential of saliva and subgingival plaque. LL-37 and Polymyxin B illustrate complementary strategies for LPS modulations and highlight the feasibility of their use as adjunctive approaches for the prevention and treatment of periodontal diseases.